2012
DOI: 10.1073/pnas.1201790109
|View full text |Cite
|
Sign up to set email alerts
|

Parasite diversity and coinfection determine pathogen infection success and host fitness

Abstract: While the importance of changes in host biodiversity for disease risk continues to gain empirical support, the influence of natural variation in parasite diversity on epidemiological outcomes remains largely overlooked. Here, we combined field infection data from 2,191 amphibian hosts representing 158 parasite assemblages with mechanistic experiments to evaluate the influence of parasite richness on both parasite transmission and host fitness. Using a guild of larval trematode parasites (six species) and an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 159 publications
(169 citation statements)
references
References 56 publications
4
164
1
Order By: Relevance
“…Although an increasing number of studies have reported negative correlations between host diversity and disease risk (29,38,39), the hidden effects of concurrent changes in parasite communities have rarely been explored (19,31,40). Future studies examining the biodiversity-disease relationship should focus more heavily on the relative importance of multiple components of biodiversity (and how they covary) in driving observed patterns in disease risk (41)(42)(43), including the direct and indirect effects of hosts, nonhosts (e.g., predators and competitors), parasites, as well as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although an increasing number of studies have reported negative correlations between host diversity and disease risk (29,38,39), the hidden effects of concurrent changes in parasite communities have rarely been explored (19,31,40). Future studies examining the biodiversity-disease relationship should focus more heavily on the relative importance of multiple components of biodiversity (and how they covary) in driving observed patterns in disease risk (41)(42)(43), including the direct and indirect effects of hosts, nonhosts (e.g., predators and competitors), parasites, as well as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in diversity will tend to reduce disease when high-competence host species and highvirulence parasites dominate in low-richness assemblages, with progressive decreases in disease as less-competent hosts and lower-virulence parasites are added. Although our experiments used realistic patterns of host and parasite assembly (15,19), the predictability of patterns involving host-parasite coassembly will be a key factor in determining the outcome of the diversity-disease relationship in other systems. If host communities assemble randomly with respect to competence (e.g., owing to stochastic or legacy-driven effects), for instance, but parasites assemble in order of increasing virulence, variation in parasite diversity will more sharply regulate disease risk than will host diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations